Strategi Pembinaan Sikap Moderasi Beragama Mahasiswa Perguruan Tinggi Keagamaan Islam Negeri - Tuala, Riyuzen Praja; Wachidah, Nor Rochmatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research is motivated by two things. First, theoretical facts state that every religion carries a mission of peace and salvation for all (rahmatan lil alamin), upholds human dignity, balance, justice and humanity. Second, the development of science and technology has led to an increase in human ability to understand religious texts. This research aims to find out, analyze and describe strategies, supporting and inhibiting factors in fostering attitudes of religious moderation in Islamic Religious College students at UIN Raden Intan Lampung. Type of qualitative descriptive research. Data was collected using interview and documentation methods. Data analysis was carried out using data reduction techniques, data presentation and drawing conclusions. Test the validity of the data using source triangulation. Research findings show that there are three strategies for fostering religious moderation attitudes of UIN Raden Intan Lampung students. First, the outdoor-indoor activity strategy is implemented in the form of moderation camp activities and outreach to strengthen religious moderation. Second, the modeling strategy is carried out by selecting student figures who are active in student organizations and UKM and have exemplary potential. Third, a holistic education strategy, carried out by providing coaching material referring to PMA number 93 of 2022 and studied from various scientific perspectives and real experiences in society. Supporting factors include the support of the Indonesian Ministry of Religion, the high commitment of the leadership of UIN RIL. Inhibiting factors include resistance from some senior student organizations who want balanced representation of participation in activities for all internal campus organizations. This is not in line with the available budget capabilities. The number of UIN Raden Intan Lampung students is quite large, and the majority of them come from general secondary schools, causing the implementation of the religious moderation development program to take quite a long time. Likewise, students' different religious understanding backgrounds require varied methods, a balanced number of resource persons/instructors/coaches/mentors with adequate religious moderation competence.